MACLimbs: human peripheral anatomy and kinesiology implemented by HyperCard. - Furman, M. B. (American Medical Informatics Association, 1991)
Physicians in various subspecialties routinely perform physical examinations of the back and extremities utilizing their understanding of peripheral anatomy, extremity kinesiology, and neuro- musculo-ligamentous pathologies. We are developing a HyperCard computer application which combines text, graphics, and sound to teach, review, and test functional limb anatomy and kinesiology in an independent, non-confrontational, user-friendly environment. The software incorporates principles which maximize learning, runs on hardware accessible to most people, encourages independent learning and self evaluation, and utilizes links which take advantage of the network structure inherent to anatomy.